Bajki funkcjonalistów - Skalski, Tadeusz (Acta Universitatis Lodziensis. Folia Philosophica. Ethica-Aesthetica-Practica, 2011)
One of the most controversial principles of contemporary functionalism is the so-called principle of organizational invariance. Roughly speaking it states that all systems with the same fine grained functional organization have the same conscious experience. The author of this article tries to show that the principle leads to absurdity.